Turkey : First and Second Reviews Under the Stand-By Arrangement, and Request for Waiver of Nonobservance of Performance Criteria and Rephasing of Purchases; Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Turkey. (IMF Staff Country Reports; Country Report ;, 2006)
Prudent macroeconomic policies helped Turkey to achieve economic growth under the Stand-By Arrangement. Executive Directors welcomed this development and stressed the need to widen the account deficit. They emphasized the need of a strong budget, powerful monetary and fiscal policies, and structural reforms to sustain economic growth and reduce vulnerabilities. They urged to strengthen the banking supervision and international reserves. They welcomed the revised program and agreed that its full implementation would help in sustaining economic growth.